2021
DOI: 10.3389/fncel.2020.540669
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Caspase-1 Ameliorates Ischemia-Associated Blood-Brain Barrier Dysfunction and Integrity by Suppressing Pyroptosis Activation

Abstract: Ischemic cerebral infarction represents a significant cause of disability and death worldwide. Caspase-1 is activated by the NLRP3/ASC pathway and inflammasomes, thus triggering pyroptosis, a programmed cell death. In particular, this death is mediated by gasdermin D (GSDMD), which induces secretion of interleukin (IL)-1β and IL-18. Accordingly, inhibition of caspase-1 prevents the development and worsening of multiple neurodegenerative diseases. However, it is not clear whether inhibition of caspase-1 can pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Caspase-1 expression was considerably enhanced after ischemic stroke as a critical molecule in initiating pyroptosis, and its suppression resulted in neuroprotection against I/R injury. It has been reported that vx-765, an inhibitor of caspase-1, can ameliorate blood-brain-barrier dysfunction and integrity after I/R injury [ 26 ]. GSDMD is an essential factor in pyroptosis, and its role has been reported in I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 expression was considerably enhanced after ischemic stroke as a critical molecule in initiating pyroptosis, and its suppression resulted in neuroprotection against I/R injury. It has been reported that vx-765, an inhibitor of caspase-1, can ameliorate blood-brain-barrier dysfunction and integrity after I/R injury [ 26 ]. GSDMD is an essential factor in pyroptosis, and its role has been reported in I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…330,433,434 VX-765, a caspase-1 inhibitor, can ameliorate infarct volumes, neurological deficits, and neuronal injury after MCAO. 435 The specific NLRP3 inflammasome inhibitor MCC950 significantly improved neurologic outcomes and reduced infarct volume when administered before or after MCAO. 436 Studies have also shown that meisoindigo, a generally water soluble and well-tolerated second-generation indirubin derivative, reduces inflammation by inhibiting leukocyte chemotaxis and migration.…”
Section: Targeting Pyroptosismentioning
confidence: 96%
“…As an important inflammatory regulator of CI, HIF-1α can stimulate the activation of the NLRP3 inflammasome [12]. However, overactivation of the NLRP3 inflammasome triggers a series of caspase 1 signaling cascades and intensifies the release of IL-1β and IL-18, leading to the formation of a vicious cycle and aggravating CI [33][34][35]. Additionally, IL-6 and TNF-α play a crucial role in the inflammatory responses induced by CI [13].…”
Section: Discussionmentioning
confidence: 99%